Analisis Pemecahan Masalah Berdasarkan Teori Pemrosesan Informasi - Nurhayati Nurhayati; Nizlel Huda; Suratno Suratno (Universitas Batanghari Jambi, 2020)
The purpose of this study is to describe students' thought processes in solving mathematical problems based on information processing theory. This research is a descriptive study with a qualitative approach that uses data collection techniques using the method of think aloud and interviews. The instrument in this study used written test questions and interview guidelines. The subjects in this study consisted of one high ability person, one moderate ability student and one low ability student. The results showed that information or stimulus in the form of questions received by students with high, medium, and low mathematical abilities entered the sensory register through the sense of sight and sense of hearing. Then attention occurs after reading the problem and perception arises. Next, students realize perception by retrieval the concepts needed from long term memory to solve problems. When conducting a retrieval of students with moderate mathematical abilities, there is a student who experiences a retrieval failure in explaining the concept. Then for students who have low mathematical ability, the concepts needed for short term memory are not stored well by long term memory, so students often experience errors and forget.